Regimes of Social Cohesion - Green, A. author. aut Link
IX, 248 p.
Keywords: In an original, and highly interdisciplinary, mixed method approach, Green and Janmaat identify four major traditions of social cohesion in developed societies, analyzing how these various mechanisms are withstanding the strains of the current global financial crisis.